Phonological and non-phonological errors at Tuvan-Russian bilingualism - Seglenmej, Svetlana F.; Saida V. Kechil-ool, Irina D.-o. Dambyra, Shenne S. Chadamba, Kira A.-o. Sat, Aleftina V. Taryma (Opción, 2019)
The formation of mechanisms that ensure speech activity in the language under study occurs to the conditions of interference, between the similarity and the difference inherent in the primary and secondary language systems, is peculiarly manifested. The article analyzes the influence of native (Tuvan) language in teaching the phonetics of the Russian language. The contrasting features of the sound structure of both languages are characterized as the point of view of a hard-to-translate interference. The study, taking into account similar and different in two languages, made it possible to diagnose difficulties and solve the problem of countering interference correctly.